Seaweed Proteins: A Step towards Sustainability? - Pereira, Leonel (2024)
This review delves into the burgeoning field of seaweed proteins as promising alternative sources of protein. With global demand escalating and concerns over traditional protein sources' sustainability and ethics, seaweed emerges as a viable solution, offering a high protein content and minimal environmental impacts. Exploring the nutritional composition, extraction methods, functional properties, and potential health benefits of seaweed proteins, this review provides a comprehensive understanding. Seaweed contains essential amino acids, vitamins, minerals, and antioxidants. Its protein content ranges from 11% to 32% of dry weight, making it valuable for diverse dietary preferences, including vegetarian and vegan diets. Furthermore, this review underscores the sustainability and environmental advantages of seaweed protein production compared to traditional sources. Seaweed cultivation requires minimal resources, mitigating environmental issues like ocean acidification. As the review delves into specific seaweed types, extraction methodologies, and functional properties, it highlights the versatility of seaweed proteins in various food products, including plant-based meats, dairy alternatives, and nutritional supplements. Additionally, it discusses the potential health benefits associated with seaweed proteins, such as their unique amino acid profile and bioactive compounds. Overall, this review aims to provide insights into seaweed proteins' potential applications and their role in addressing global protein needs sustainably.